Comportamiento de diferentes variedades de soya en la granja santa Inés Universidad Técnica de Machala - Merchan Marquez, Margoth Valeria (2018)
Soy (Glycine max (L.) Merr.) Is a legume of greater importance worldwide for its large number of uses, due to its high content of protein and energy, since on average, the dry grain contains 20% oil and 40% protein. In Ecuador, its importance lies in the production of balanced feed and its representativeness in the trade balance, because the imports of this product are significant. Currently in the country has a production of 26,280 ha, with a production of 41,788 tons. The importance of soybeans derives mainly from its small relation with the food issue and from being a good soil conservator since it contributes nitrogen to it. The research work was carried out at the Santa Inés Experimental Farm belonging to the Academic Unit of Agricultural Sciences of the Technical University of Machala. This investigation was carried out in order to evaluate the behavior of two varieties of soybean under different population densities in the Santa Inés Farm, evaluating the behavior of INIAP 303 and INIAP 304 varieties planted at 40x10 and 40x20 cm depending on the morphological parameters of the culture The experimental design used was a Latin table with 4 treatments and 4 repetitions, using two different sowing densities of 10 and 2 centimeters respectively, with a linear length of 3 meters; the width of the plot was of 1.60 meters with furrows of 0.40 centimeters, using a system of sowing in espeque. The genetic material was evaluated based on agronomic characteristics and yields of the lines. The data were recorded in five plants taken at random from each useful plot. The variables evaluated were height of load (cm), pods per plant, seeds per plant, grains per pods, weight of 100 seeds and yield. We observed the results obtained in the Ducan test for the case of the variable height of the pod indicates that treatment 2 (Variety INIAP 303 and 40x20) reaches the best development of culture (6.80 cm), which is different statistically the other treatments evaluated, the case of the variable height of the plant to the harvest indicates that the treatment 3 (Variety INIAP 304 and 40x10) reaches the highest height of culture (35.90 cm), which is statistical difference with the other treatments evaluated, for the case of the variable number of pods per plant tells us that treatment 3 (Variety INIAP 304 and 40x10) is the one that reached the best average with 49.30 pods per plant, which is different statistical with the other treatments evaluated, while the variable seeds per pod indicates that treatment 1 (Variety INIAP 303 and 40x10) reached the same average of seeds per pod as in treatment 2 (Variety INIAP 303 and 40x20) with 2.90 s shells by pod.